The Yanbu'a Method by KH. Arwani Amin's Son in Reading, Memorizing and Writing the Qur'an (Descriptive Study of the Development of the Qur'an Learning Methodology) - Mohammad Fattah; Ardiani Ardiani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The Qur'an is a noble holy book, revealed to the Prophet Muhammad SAW, in the month of Ramadan and on the night of Lailatul Qadar, everything will become noble if it is paired with something noble too. Indonesia is a country with a majority Muslim population and the Qur'an as a guide to life for mankind must be studied by every Muslim and Muslimah. The focus in this study are: 1. What is the significance of Yanbu'a Method by the son of KH. Arwani Amin in recitation, pronounciation the Qur’an and writing. 2. What are the advantages and disadvantages of Yanbu'a Method by the son of KH. Arwani Amin in reciting, pronounciation of the Qur'an and writing? 3. What are the Benefits and Uses of Yanbu'a Method by the son of KH. Arwani Amin on the ability to recite, memorize the Qur'an and writing. The author uses a descriptive qualitative approach. Meanwhile, the type of research uses library research, namely efforts that refer based on books, articles, journals, and other materials that help with a problem that will be studied by researchers. The data analysis technique used in this research uses critical analysis. The result of this research is that the Yanbu'a Method is one of the methods for learning the Qur'an starting from reading, writing and memorizing the Qur'an for children and adults with a fast time because it is easier for all people to understand. Learning Al-Qur'an Yanbu'a method has significant benefits for students' reading of Al-Qur'an it is from a increase in the reading of students who initially did not recognize the hijaiyah letters to many students who have learned tajweed but cannot apply it when reading the Qur'an. The Yanbu'a Method has advantages that other Qur'an learning methods do not have such as the Yanbu'a Method not only includes reading learning but is equipped with learning to write and memorize the Qur'an along with understanding tajweed, Makharij al-Huruf and Sifat al-Huruf. Therefore, the Yanbu'a Method is a solution for people who want to accelerate proficiency in reading the Qur'an so that the Yanbu'a Method is the first choice.